Musical Experimentation Based on the Use of Symbols of National Affiliation. Baiuca: Electronic and Galician Traditional Music - Pérez-Borrajo, Aarón; Matas de Íscar, Irene (Madrygal. Revista de Estudios Gallegos, 2023)
Baiuca is the result of the irruption in the Galician music scene of initiatives based on the updating of traditional Galician music through the application of new musical languages and processes of symbolic resignification. A solo project by Alejandro Guillán together with artists and groups such as Adrián Canoura, Xosé Lois Romero e Aliboria, Baiuca proposes a revolution within this field, promoting the recovery of rhythms, melodies and timbres typical of the country. Its ultimate aim is to bring this musical dimension to a new audience, located in new spaces and contexts, by the use of alternative and non-conventional means. Both on the sound and the audio- visual level, the use and deliberate appropriation of symbols of national affiliation is evident, which becomes a sign of identity of this artistic-musical project. Therefore, the main objective of this article is to reflect on the ideological and cultural load that surrounds this initiative. Based on the case study of songs such as “Muíño”, included in the album Solpor (2018), we will delve into the theoretical-musical basis and the cultural approach from which Guillán departs. In short, we intend to go into the analysis of a “revolutionary” musical project that, inevitably, is built on the same cultural and national stereotypes with which it seeks to break.